2020
DOI: 10.1002/nau.24451
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral comorbidity, overweight, and obesity in children with incontinence: An analysis of 1638 cases

Abstract: Aims Children with nocturnal enuresis (NE), daytime urinary incontinence (DUI), and fecal incontinence (FI) are at risk for behavioral problems, overweight, and obesity. The aim of this study was to analyze the specific behavioral and weight comorbidity in subtypes of incontinence. Methods A total of 1638 consecutive patients presented to a tertiary incontinence clinic from 2012 to 2018 was examined prospectively according to ICCS criteria. Behavioral symptoms were measured with the Child Behavior Checklist (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The effect of psychological factors on the development and persistence of fecal incontinence is debatable. Nevertheless, incontinence in children and adolescents with neurodevelopmental and psychological disorders is common and vice versa (8,9). Treating incontinence can reduce the severity of psychological disor-ders (7).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of psychological factors on the development and persistence of fecal incontinence is debatable. Nevertheless, incontinence in children and adolescents with neurodevelopmental and psychological disorders is common and vice versa (8,9). Treating incontinence can reduce the severity of psychological disor-ders (7).…”
Section: Introductionmentioning
confidence: 99%
“…The study by Wagner et al (23) also concluded that being overweight or obese gives you a significant higher risk of developing OAB symptoms, especially urinary incontinence (p = 0.017). A recent study by von Gontard et al (24) supported the theory that behavioral symptoms, psychiatric disorders, and being overweight/obese were risk factors associated with urinary incontinence. However, we did not observe a significantly higher risk of daytime incontinence in obese children and adolescents in the current study.…”
Section: Discussionmentioning
confidence: 87%
“…The obesity seems to be an important risk factor associated with incontinence, but the interaction between these factors is complex and needs further investigation [117].…”
Section: It Is Recommended To Assess Kidney Function In Children and ...mentioning
confidence: 99%